2019
DOI: 10.1111/hiv.12818
|View full text |Cite
|
Sign up to set email alerts
|

HIV self‐testing intervention experiences and kit usability: results from a qualitative study among men who have sex with men in the SELPHI (Self‐Testing Public Health Intervention) randomized controlled trial in England and Wales

Abstract: Objectives SELPHI (HIV Self‐Testing Public Health Intervention) is the largest randomized controlled trial (RCT) of HIV self‐testing (HIVST) in a high‐income setting to date, and has recruited 10 000 men who have sex with men (cis‐ and transgender) and transgender women who have sex with men. This qualitative substudy aimed to explore how those utilizing self‐tests experience HIVST and the implications for further intervention development and scale‐up. This is the first qualitative study in Europe investigatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 24 publications
0
41
0
Order By: Relevance
“…All kits distributed through SELPHI were BioSure™ 2 nd generation blood based HIVSTs. Full descriptions of the interventions and theoretical underpinnings can be found in prior publications [ 19 , 23 , 24 ]. Here we present an abridged version.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All kits distributed through SELPHI were BioSure™ 2 nd generation blood based HIVSTs. Full descriptions of the interventions and theoretical underpinnings can be found in prior publications [ 19 , 23 , 24 ]. Here we present an abridged version.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis combined framework and thematic approaches [26,27]. Our framework drew from emerging themes identified during data generation, the wider literature around trans peoples' experiences of HIVST / sexual health services, theorised key components of intervention acceptability from formative and RCT acceptability work and systematic reviews [18,23,[28][29][30]. The analysis framework can be found in additional file 3.…”
Section: Interviews and Data Analysismentioning
confidence: 99%
“…Finally, some outcomes of interest were not recorded in specific population groups. Adverse events were not reported in RCTs recruiting MSM and trans people (although numerous studies have shown that HIVST is highly acceptable for this group [10,11,35,40,[42][43][44][45][46]). Condom use outcomes were collected mainly in RCTs among MSM, with only one RCT reporting on inconsistent condom use for FSW [28].…”
Section: Evidence Gapsmentioning
confidence: 99%
“…The two-week follow-up was a form of enablement, increasing motivation (reflective & automatic). In the SELPHI pilot, participants reported the test kit was easy to use, that the instructions were simple and the support structures adequate for their needs [14,15], demonstrating that our efforts to ameliorate capability issues through intervention design were successful.…”
Section: Selphi Logic Modelmentioning
confidence: 99%
“…Participants in SELPHI who receive HIVST kit(s) are provided with a BioSure TM HIVST, which uses a whole blood sample. Intervention acceptability and test kit usability for SELPHI participants has been reported elsewhere [14,15].…”
Section: Selphi Hiv Self-testing Rctmentioning
confidence: 99%